A venture in self-reliance, 1958-1968 - United Nations ([New York, United Nations, 1968)
The social and economic situations in Africa when the commission was established.
On cover: Ten years of ECA, 1958-1968.
aia 13/02/2019
Loans
Keywords: Africa-- United Conditions; Africa